The Role and Performance of Farmer Group in Organic Vegetable Business - Mubarokah, Mubarokah; Rizkiyah, Noor; Santoso, Wahyu; Sari, Putri Nurmalita (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Natural substances are used instead of synthetic chemicals in organic farming, which eschews the use of synthetic insecticides, fertilizers, and plant growth regulators. The purpose of this study is to (1) Identify the role of farmer groups in the development of organic vegetable businesses; and (2) analyze factors that affect the performance of organic vegetable farmer groups. Technique sampling set is 40 farmers Respondents were selected purposively, taking into account capacity and capability. Qualitative descriptive analysis and SEM-PLS, two data analysis techniques, are being applied. The findings of this study demonstrate how well-suited a farmer organization to play a role in organic vegetable production from upstream to downstream. External factor variables have a positive effect on performance variables but are not significant. This is due to the relatively low capacity of farmer group members due to low education. On the other hand, land size, member involvement, production facilities and member access all have an influence on community performance. The influence of community competence on performance reveals that the initial sample value, 1.146, is positive. This value indicates that there is a favorable association between the competency variable and community performance. However, when linked to the role of the group in terms of marketing access, there is still a need for additional knowledge, skills, and farmers are still very dependent on community leaders for the sale of crops, which has an impact on the fighting power of farmers.